Kajian Ontologi, Epistemologi dan Aksiologi dalam Bimbingan Konseling - Cania, Lita Fitara (Guidance and Counseling Study Program, Pattimura University, 2022)
The purpose of this article is to find out how important or urgent the study of ontology, epistemology and axiology is which is useful as a foundation in guidance and counseling where it becomes the basis for obtaining a science so that the science has been arranged logically, empirically and systematically which knowledge is These gains are manifested in the form of guidance and counseling in which the guidance and counseling process has also been systematically structured so that the knowledge of guidance and counseling is a study that studies deviant individual or client behavior that must be overcome with the help of a counselor. This writing was designed using the library method, or better known as literature study. The results of this literature review or literature review are the basis of knowledge about the study of ontology, epistemology and axiology, a basis for acquiring a science which will become science. systematically and empirically so that science has been tested for its truth. The truth of this knowledge must be based on ontology, epistemology and axiology, that is why if it has been proven by science such as guidance and counseling science, then a guidance and counseling science will be realized which in guidance and counseling science will discuss an individual or client's wrong behavior so that can be directed positively.